2023
DOI: 10.1111/pbr.13121
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the genetics of resistance to Fusarium head blight and deoxynivalenol accumulation in barley and considerations for breeding

Abstract: Fusarium head blight (FHB) or scab is a devastating disease of barley that severely reduces the yield and quality of the grain. Additionally, mycotoxins produced by the causal Fusarium species can contaminate harvested grain, resulting in food safety concerns and further economic losses. In the Upper Midwest region of the United States, Fusarium graminearum is the primary causal agent, and deoxynivalenol (DON) is the main mycotoxin associated with Fusarium infection. Deployment of resistant cultivars is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The pathogen is considered hemi-biotrophic and switches from biotrophy to necrotrophy at approximately 72 h post-infection, where Fusarium-susceptible parents may also contribute resistance alleles for low DON [ 25 ]. Numerous bi-parental studies conducted to identify FHB resistance in barley have shown that QTLs associated with FHB resistance are not always coincident with those for DON accumulation [ 6 ]. Resistance to this disease of barley may be somewhat bipartisan, associated with mechanisms of infection, and/or a reduction in mycotoxin accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogen is considered hemi-biotrophic and switches from biotrophy to necrotrophy at approximately 72 h post-infection, where Fusarium-susceptible parents may also contribute resistance alleles for low DON [ 25 ]. Numerous bi-parental studies conducted to identify FHB resistance in barley have shown that QTLs associated with FHB resistance are not always coincident with those for DON accumulation [ 6 ]. Resistance to this disease of barley may be somewhat bipartisan, associated with mechanisms of infection, and/or a reduction in mycotoxin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunity to FHB is not known in barley, and the availability of resistance sources is limited for use in breeding [ 5 ]. Unlike in other cereals such as wheat where major quantitative trait loci (QTL) have been identified, resistance in barley is conferred by many minor genes [ 6 ]. Coincidental agronomics (extreme heading; tall stature) of common resistance sources are most often undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…We found many homologs of FfR1 in various plant species including Triticum aestivum (wheat), Hordeum vulgare (barley), Aegilops tauschii , Lolium rigidum , and so on ( Figure 3 d). In wheat and barley, Fusarium head blight (FHB) is a major threat worldwide [ 58 , 59 ]. This disease is also known as scab or head blight, and is caused by Fusarium graminearum and other Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%